Interarm Systolic and Diastolic Blood Pressure Difference Is Diversely Associated With Cerebral Atherosclerosis in Noncardioembolic Stroke Patients. (26th July 2017) - Chang, Yoonkyung; Choi, Gyeong Seon; Lim, Soo Mee; Kim, Yong-Jae; Song, Tae-Jin
Abstract: BACKGROUND: Interarm systolic and diastolic blood pressure differences (IASBD, IADBD) are not infrequent in various populations. Cerebral atherosclerosis, including extracranial cerebral atherosclerosis (ECAS) and intracranial cerebral atherosclerosis (ICAS), is an important risk factor for stroke. In this study, we aimed to investigate the relationship of IASBD, IADBD with presence and burden of ICAS and ECAS. METHODS: This was a retrospective hospital-based cross-sectional study. In total, 1, 063 consecutive noncardioembolic ischemic stroke patients, who were checked for bi-brachial blood pressures from ankle–brachial index and brain magnetic resonance angiographic images of cerebral arteries, were included. The IASBD and IADBD were defined as absolute value of the blood pressure difference in both arms. RESULTS: In all included patients, patients with IASBD ≥10 and IADBD ≥10 were noted in 9.4% (100/1, 063) and 5.3% (56/1, 063). The patients with IASBD ≥10 mm Hg were more frequently burdened with ICAS ( P = 0.001) and ECAS ( P = 0.027) and patients with IADBD ≥10 mm Hg were more frequently burdened with ICAS ( P = 0.042) but not ECAS ( P = 0.187). Multivariate analysis after adjusting gender, age, and a P value <0.1 in univariate analysis showed IASBD ≥10 mm Hg was associated with the presence of both ECAS and ICAS [odds ratio (OR): 2.96, 95% confidence interval (CI): 1.65–5.31]. The IADBD ≥10 mm Hg was related with presence of ICAS only (OR: 1.87, 95% CI: 1.05–3.37) but not with ECAS only (OR: 1.50, 95% CI: 0.73–3.06). CONCLUSIONS: Our study showed IASBD and IADBD were diversely associated with cerebral atherosclerosis. In noncardioembolic stroke patients with IASBD ≥10 or IADBD ≥10, the possibility of accompanying cerebral atherosclerosis should be considered.